Economic paradoxism and meson economics - Gheorghe Săvoiu; Vasile Dinu (Amfiteatru Economic Journal, 2015)
The structure of the paper brings together three major sections, following the general approach to the impact of paradoxes in economic theory. The first section describes a necessary investigation in the synthesized universe of paradoxes, to capitalize on Quine's paradox taxonomy, and to reveal the importance of really paraconsistent paradoxes, defining, in a relative and innovative manner, economic paradoxism in the sense of excess of creative capitalization of paradoxes in the area of science, as initiated by mathematician and logician Florentin Smarandache. The second section turns into an original exposition of economics theory and the third section reveals the concept of meson economics and the principles of that economy, completed with some final remarks, some of which are conclusive, and some others interrogative, aligned to the paradox of knowledge, in keeping with which human beings are looking for answers, and finally find more and more questions.
Keywords: B23; B40; B51; B53; C50; D01; E30; N10; P10; 330; economic paradoxism; meson economics; economic theory and paraconsistent paradoxism